To find the centroid of triangle ABC, we use the formula for the centroid of a triangle given by the coordinates of its vertices \( A(x_1, y_1) \), \( B(x_2, y_2) \), and \( C(x_3, y_3) \):
\[ \text{Centroid} (G) = \left( \frac{x_1 + x_2 + x_3}{3}, \frac{y_1 + y_2 + y_3}{3} \right) \]
Given the vertices:
- \( A(-3, -3) \)
- \( B(0, 6) \)
- \( C(4, -3) \)
We can substitute the coordinates into the formula:
- Calculate the x-coordinate of the centroid:
\[ x_G = \frac{-3 + 0 + 4}{3} = \frac{1}{3} \]
- Calculate the y-coordinate of the centroid:
\[ y_G = \frac{-3 + 6 - 3}{3} = \frac{0}{3} = 0 \]
So, the centroid \( G \) of triangle ABC is:
\[ G = \left( \frac{1}{3}, 0 \right) \]
Thus, the centroid is given by the coordinates:
\[ G = \left( \frac{1}{3}, 0 \right) \]
Therefore, the correct response corresponds to:
\((\frac{1}{3}, 0)\)